Learning from a gender transformative intervention among faith-leaders in Woliso, Ethiopia: A qualitative study - Elisa Gobbo; Addise Amado Dube; Mengistu Demeke; Wosene Berhanu; Nesanet Megersa; Yoska Amenu; Adamu Addisse; Sibylle Herzig Van Wees (Global Public Health)
Violence against women and girls (VAWG) continues to be a pervasive issue globally, and in Ethiopia, that harms women and challenges progress towards a more gender-equal society. Many interrelated social, economic, and cultural factors impact VAWG. Religion is a complex factor that can contribute to and act as a preventative measure against VAWG. Thus, faith-leaders have been identified as key actors in VAWG prevention. This study examines Ethiopian Evangelical faith-leaders transformative knowledge change following a Channels of Hope for Gender training intervention. Focus group discussions were conducted with faith-leaders from five different Evangelical Church groups. The results show that the faith-leaders’ experience of the Channels of Hope training challenged their gender norms and allowed them to enact relationship and community-level changes. Additionally, they demonstrated efforts and interest in generating change at the level of the Church. However, barriers remained to fully addressing VAWG and implement gender transformative learning more widely. Thus, we conclude that the Channels for Hope training is useful in generating mindset changes and improving relationship-level interactions, but that it requires a longer implementation timeframe and further support from other structures and interventions to achieve sustainable change to prevent VAWG.